Trucks Roll! - Lyon, George Ella, 1949-; Frazier, Craig, 1955- (New York : Atheneum Books for Young Readers, 2007)
Illustrations and simple, rhyming text reveal many different--and sometimes silly--items that trucks can haul.
"A Richard Jackson book."
Keywords: Trucks -- Juvenile fiction; Stories in rhyme